(untitled) (Contemporary Mathematics, 2025)
In the present paper, we study the linear stability of perturbations around the Couette flow for a two dimensional compressible non-isentropic Euler-Poisson system in the domain . A Lyapunov type instability result for the density and the temperature is obtained, and in particular, the inviscid damping for the solenoidal component of the velocity field is proved.